Transcriptional pulse-chase analysis reveals a role for a novel snRNP-associated protein in the manufacture of spliceosomal snRNPs. - Noble, S M (1996)
Vertebrate spliceosomal snRNAs associate with a conserved set of proteins, the Sm proteins, via a conserved RNA sequence, the Sm site. Assembly of this complex is required for the accumulation of stable snRNPs, hypermethylation of the 5' cap structure and nuclear import of the resultant particles. The function of individual core snRNP proteins is poorly understood, in part because of the difficulty of selectively inactivating individual polypeptides in vivo. Using a transcriptional pulse-chase method we have defined for the first time the steps of snRNP biogenesis in Saccharomyces cerevisiae. We describe a novel component of spliceosomal snRNPs, Brr1, which is distinct in sequence from Sm core proteins and yet which shares many of their properties, as well as a genetic interaction with the yeast homolog of Sm D1 core protein. Through a kinetic analysis of snRNP formation in wild-type and brr1 mutant cells we demonstrate specific defects in a subset of steps in the brr1 mutant: newly synthesized snRNAs are destabilized and 3'-end processing is slowed, whereas the cap hypermethylation reaction is unaffected. Notably, the stability of mature particles, as measured by promoter shut-off experiments, is normal in the absence of the Brr1 snRNP protein.